Mediastinal lymph node dissection effectiveness in patients with I stage of non-small cell lung cancer - A. P. Kolesnik (Zaporozhye State Medical University, 2014)
Introduction. Treatment of patients with lung cancer remains a difficult problem of oncology. Disputable questions are using endoscopic technique, possibility of segmentectomy, determination of volume of lymph dissection. The aim of the study was to conduct the effectiveness analysis of different volume of lymph dissection of mediastinum in patients with Stage I non-small cell lung cancer (NSCLC). Materials and methods. Study was conducted in the Thoracic Surgery department of Zaporizhzhya Regional Clinically Oncologic Dispensary. 133 patients with Stage I NSCLC were included from December 2008 till January 2013. There were 113 men and 20 women. For every patient surgical treatment was performed: lobectomy (n=92) and pneumonectomy (n=41). By performed lymph dissection patients were divided into two groups. Group 1 - patients with incomplete mediastinal lymph node dissection (ICMLD) (n=91), group 2 - patients who underwent complete, systematic mediastinal lymph node dissection (CSMLD) (n=42). After removal of the specimen (the part of the lung, as well as tissue with mediastinal lymph nodes), histological and immunohistochemical studies were performed. Immunohistochemical study was performed on paraffin sections of lung tumors using monoclonal antibodies to Ki-67, CD31, p53 , E-Cadherin, EGFR, c-erbB-2 , pantcytokeratin and visualization system EnVision FLEX. The final staging was performed after morphological study (pTNM). Adjuvant chemotherapy was conducted for 40 patients, 90 patients did not receive additional treatment after surgery. 3-4 cycles of chemotherapy were conducted according to the scheme: cisplatin 80 mg/m2 day 1 cycle and etoposide 120 mg/m2 on 1-3 days of the cycle. Chemotherapy was started no later than 1 month after surgery. Period of observation was 27,1±17,2 months. Data on the survival of patients was obtained by analyzing patients and outpatients data of Regional Cancer Registry. Statistical processing was performed using Statistica 6.0 (license number AXXR712D833214FAN5). Level of p<0.05 was considered statistically significant. Results. The cause of death in patients after ICMLD in 11 cases was distant metastases (brain (n=3) , bone (n=4) , liver (n=2) , lung (n=2)) and 7 cases relapse in the mediastinum with subsequent spread to the nodes in the neck. In patients with CMLD recurrences in the mediastinum became cause of death in 6 cases. Survival of patients with stage I NSCLC who underwent CMLD during surgery depended on the adjuvant treatment, the expression of p53, EGFR, Her-2/neu, pancytokeratine. In patients who underwent ICMLD survival was influenced by the volume of removed lung parenchyma (lobectomy, pneumonectomy), the expression of Ki-67, p53, EGFR, Her-2/neu. The deterioration of survival of patients who underwent pneumonectomy with ICMLD in comparison with patients after pneumonectomy with CMLD (p=0.002) was noted. In patients after adjuvant chemotherapy and CMLD survival was worse as compared to patients who underwent CMLD and adjuvant chemotherapy was not performed (p=0.03). Significantly worse survival is noted in patients after ICMLD with high-level expression of Ki-67, p53 (≥25%) than in patients who underwent CMLD with similar molecular characteristics of the tumor. Data analysis also indicated worsening of survival of patients with the high level expression of EGFR, Her-2/neu, regardless of the lymph dissection level. Analysis of the data confirmed the worst survival of patients after pneumonectomy with ICMLD. So the annual survival of the specified group of patients was 53%±16%, whereas in patients who underwent CMLD comparable figure was 93%±5%. In patients who underwent additional CMLD+adjuvant chemotherapy survival after treatment was lower than in patients without postoperative chemotherapy. It is necessary to continue the study of the relationship and the level of efficiency of lymph dissection and adjuvant chemotherapy in patients with early-stage NSCLC to determine the causes of this pattern. Conducting CMLD in patients with high expression of Ki-67 allows achieving annual survival of 93%±7%, whereas in those with NPMLD the figure is 81%±6%. Just CMLD can improve survival in patients with stage I-NSCLC and p53 overexpression. Year survival was statistically significantly different in patients with CMLD and ICMLD (p<0.01). Conclusions. Conducting mediastinal lymph dissection in volume of CMLD improves survival in patients with stage I of NSCLC with the pneumonectomy, as well as in over expression of Ki-67 and p53. Survival of patients after surgical treatment with CMLD and additional postoperative chemotherapy was worse than the long-term outcomes in patients with CMLD without postoperative chemotherapy (p=0.03). The results of the study indicate the need for further study of the issue of individualization of surgical treatment of patients with early-stage NSCLC, depending on the clinical and morphological characteristics of the patient and the tumor.